COVID-19 transmission and the safety of air travel during the pandemic: a scoping review - Khatib, Aisha N.; McGuinness, Sarah; Wilder-Smith, Annelies (Current opinion in infectious diseases, 2021)
Purpose of review To examine the literature assessing safety of air travel relating to coronavirus disease 2019 (COVID-19) transmission from January 2020 to May 2021. The COVID-19 pandemic has had an unprecedented impact on air travel and global mobility, and various efforts are being implemented to determine a safe way forward. As the pandemic evolves, so do the challenges that force various stakeholders, including the aviation industry, health authorities, and governments, to reassess and adapt their practices to ensure the safety of travellers. Recent findings The literature was reviewed for multiple aspects of air travel safety during the COVID-19 pandemic. Recurring themes that surfaced included the pivotal role of commercial air travel in the geographic spread of COVID-19, the efficacy of travel restrictions and quarantines, inflight transmission risk and the role of preventive measures, the utility of pre and post flight testing, the development of effective vaccines and subsequent challenges of vaccine passports, and the ongoing threat of novel highly transmissible variants. Much uncertainty lies ahead within the domains of these findings, and ongoing research, discourse and review will be necessary to navigate and determine the future direction and safety of air travel. Recovery will be slow, necessitating innovative, multipronged and collaborative solutions.